Fructose Intake and Its Correlation with Carotid Intima-Media Thickness in Male Employees with Hypercholesterolemia in Harapan Kita National Cardiovascular Center Hospital, Jakarta, Indonesia - Astiti Dwi Arumbakti; Saptawati Bardosono (World Nutrition Journal, 2019)
Cardiovascular disease is the number one cause of death worldwide with an increasing prevalence annually. Atherosclerosis is the main cause of cardiovascular disease that is detectable early by ultrasound examination of the intima-media thickness (IMT) of the carotid artery. One of the modifiable risk factors for developing atherosclerosis is dyslipidemia, that can be affected by food intake among them is high fructose diet. Apart from naturally occurring, fructose is largely used commercially as food/beverage sweetener. This cross sectional study was conducted to investigate the correlation between fructose intake and IMT in male subjects with hypercholesterolemia aged 19–49 years old. Of 47 subjects who are Harapan Kita National Cardiovascular Center Hospital’s employee, median age was 41 (33–45) years old. In 57.4% subjects, low density lipoprotein (LDL) was found high and very high, 29.8% subjects have low high density lipoprotein (HDL) levels, and 27.6% subjects have high and very high triglycerides levels. Most subjects have normal systolic and diastolic blood pressure. Around 72.3% subjects were classified as obese and 66.0% were classified as having central obesity. Majority of subjects were light smoker and 49.8% of them performed light activity. In carotid IMT carotid examination, median of 1 (0.8–1.4) mm was found with 63.8% subjects developed thickness. Median total energy intake was 1209 (1020–1645) Kcal/day, mostly with adequate carbohydrate, protein, and fat, fiber intake was inadequate in 100% subjects, and mean fructose intake of 31,97 ± 15,48 gram/day. Bivariate analysis did not demonstrate any correlation between fructose intake and carotid IMT however there was positive correlation between waist circumference and fat intake with carotid IMT. Multivariate analysis showed that fat intake has a significant correlation with carotid IMT. Key words: atherosclerosis, fructose, hypercholesterolemia, intima-media thickness